Effect of test interruptions on blood lactate during constant workload testing - Beneke, R.; Hutler, M.; von Duvillard, S. P.; Sellens, M.; Leithauser, R. M. (Medicine & Science in Sports & Exercise, 2003)
OBJECTIVE: To determine whether repetitive test interruptions (TI) during constant load testing influence blood lactate concentration (BLC), maximal lactate steady state (MLSS), MLSS workload (P-MLSS), and relative MLSS intensity (Int-MLSS). METHODS: Nineteen males participated in this study. In experiment A, 10 subjects (27.5 +/- 2.9 yr; 183.7 +/- 5.2 cm; 77.4 +/- 3.7 kg) performed 30-min constant load tests: one without TI, one with TI of 30 s, and one with TI of 90 s after every 5 min of cycling at a given workload. In experiment B, nine subjects (28.0 +/- 2.7 yr; 182.9 +/- 6.8 cm; 76.2 +/- 4.5 kg) performed 30-min constant load tests at different workloads until MLSS had been determined for all three TI protocols. RESULTS: In experiment A, the BLC after 30 min net working time (BLC30) was higher (P < 0.001) without TI (6.0 +/- 1.3 mmol.l(-1)) than with TI of 30 s (4.9 +/- 1.4 mmol.l(-1)) or 90 s (4.5 +/- 1.1 mmol.l(-1)). The change in BLC during the final 20 min (DeltaBLC10-30) was greater (P < 0.01) without TI (1.2 +/- 1.0 mmol.l(-1)) than with TI of 30 s (0.2 +/- 0.7 mmol.l(-1)) or 90 s (-0.3 +/- 0.7 mmol.l(-1)). In experiment B, the MLSS was not affected, but P-MLSS and Int-MLSS were lower (P < 0.01) without TI (277.8 +/- 24.4W and 73.7 +/- 7.6%) than with TI of 30 s (300.4 +/- 30.4W and 79.2 +/- 8.0%) or 90 s (310.0 +/- 31.2W and 81.5 +/- 7.1%). Approximately 35% of the variance of BLC30 and DeltaBLC10-30, and 70% of the variance of P-MLSS and Int-MLSS were explained by TI duration (P < 0.001). CONCLUSIONS: TI decreased BLC30 and DeltaBLC10-30 but has no effect on MLSS. Consequently, with TI, the MLSS is achieved at higher P-MLSS and Int-MLSS.